Opinión de expertos y entrenadores sobre el reglamento de la competición infantil en baloncesto - Ortega Toro, E.; Pinar, M. I.; Salado Tarodo, J.; Palao, J. M.; Gomez Ruano, M. A. (Revista Internacional de Ciencias del Deporte, 2012)
The aim of this study is to analyze the opinion of the coaches and experts on rule modification in basketball under-14. For this questionnaire was administered to Modify Competition to a total of 101 coaches, and 14 experts. The most significant results indicates that: a) the 85.7% of the coaches and 78.6% of the experts a rule change, b) prohibit coaches the opportunity to defend in zone c) the experts would change the height of the basket, decrease the size of the ball, come close the three point line, victories would change the system, eliminate the zone defense, and eliminate the KO. All these data should be used to make a deep reflection and future studies on the current state of competition regulation in children, with the aim of adapting to the young sport, and not the children who have to adapt to the sport.